Analisis Kualitas Pelaporan Keuangan Ditinjau Dari Sistem Informasi Akuntansi, Sistem Pengendalian Internal, Dan Kompetensi Sumber Daya Manusia - Ashari, Niken Wulan; Dewi, Maya Widyana; Pardanawati, Sri Laksmi (Jurnal Ilmiah Keuangan Akuntansi Bisnis, 2025)
This study aims to examine the effect of accounting information systems, government internal control systems, and human resource competence on the quality of local government financial reporting. The population consists of employees responsible for financial administration and accounting functions in 35 Regional Apparatus Organizations (OPD) of Sukoharjo Regency, with a sample of 60 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed with multiple linear regression, supported by validity, reliability, and classical assumption tests. The findings reveal that accounting information systems and human resource competence have a significant positive effect on financial reporting quality, while the government’s internal control system has no significant effect. These results highlight the importance of strengthening accounting information systems and enhancing human resource competence to achieve transparent and accountable local government financial reporting.